Voices and silencing in Veja and Época: the political use of sources on the World Cup coverage in an election year (RuMoRes, 2018)
This article analyzes discursive strategies used in the field of magazine journalism, to express and form the public opinion in a context of World Cup and presidential elections in Brazil. For such, we analyzed the discourse of ordinary people on the coverage made by the magazines Época and Veja. Thus, using framing analysis we could perceive the political use of those discourses, and in a few moments, their silencing.